2017
DOI: 10.1155/2017/4263017
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Neovascular Age-Related Macular Degeneration with Anti-VEGF Agents: Predictive Factors of Long-Term Visual Outcomes

Abstract: Purpose To evaluate the predictive factors of long-term visual outcomes in neovascular age-related macular degeneration (nAMD) treated with antivascular endothelial growth factor (anti-VEGF) agents. Methods Unicentric retrospective review of patients with nAMD treated with anti-VEGF agents. Visual outcomes, 12 and 60 months after diagnosis, were evaluated. In an attempt to identify predictive factors of visual outcomes, multiple variables (demographic and epidemiological characteristics, angiographic and tomog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 12 publications
2
17
0
Order By: Relevance
“…It is suggested that the response to treatment could also be affected by the baseline vision, due to a phenomenon known as the ceiling effect, whereby subjects with a worse baseline BCVA were less likely to lose further vision and subjects with better BCVA were less likely to improve [44, 45]. This has also been observed in large studies, including the MARINA [46] and ANCHOR [47] studies which reported that the baseline BCVA is a strong predictor of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that the response to treatment could also be affected by the baseline vision, due to a phenomenon known as the ceiling effect, whereby subjects with a worse baseline BCVA were less likely to lose further vision and subjects with better BCVA were less likely to improve [44, 45]. This has also been observed in large studies, including the MARINA [46] and ANCHOR [47] studies which reported that the baseline BCVA is a strong predictor of treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascular age-related macular degeneration (AMD) is one of the primary causes of visual loss in developed countries [1]. Although the advent of antivascular endothelial growth factor (VEGF) therapy has revolutionized treatment for this condition, the long-term visual outcome is still limited in some patients [24].…”
Section: Introductionmentioning
confidence: 99%
“… 14 However, in the real-life setting, from which data are reported here, treatment was adjusted to the response, implying that patients with a more modest treatment effect also received more injections. 7 In accordance with this, derived variables, such as the follow-up time and the number of visits, and thereby also the control interval, had no separate influence on the treatment response. The real-life setting implied that all patients were treated, 15 and thus the average therapeutic response was more moderate than in RCTs performed on selected patient materials.…”
Section: Discussionmentioning
confidence: 76%
“…However, with access to large data sets, this lack of homogeneity gives the opportunity to study the contribution of individual risk factors to the outcome of the treatment. A recent study of real-life experience with anti-VEGF treatment in wAMD had a long follow-up, 7 but the study was retrospective, patient selection due to death or discontinuation of follow-up was not accounted for, and the study was powered only for the study of a few variables.…”
Section: Introductionmentioning
confidence: 99%